A holistic approach to evaluate building performance gap of green office buildings: A case study in China. (15th May 2020) - Wu, Xiaoying; Lin, Borong; Papachristos, George; Liu, Pei; Zimmermann, Nici
Abstract: The rapid development of green buildings world widely has not delivered the anticipated energy related benefits because the real performance of green buildings is not as good as expected. This paper presents a building case study in China by applying a holistic approach which integrates system dynamics and energy performance simulation to evaluate the building performance gap and provide management strategies to minimize the performance gap. The case study in this paper is an office building located in Shanghai, which was awarded "Three Star" in Evaluation Standard for Green Buildings in China (GB/T 50378–2006). Several scenarios including six single management strategy scenarios and four multiple management strategy scenarios are carried out and in each scenario, building performance is analyzed qualitatively in terms of project quality (ranging from 0 to 1), and quantitatively in terms of energy use intensity (kWh/m 2 ). The results of this case study are compared to another green office building located in the UK. The cross case mismatch between qualitative and quantitative results is due to four factors that performed better in reality that they were designed. It is demonstrated that multiple factors could help to increase building performance more than single factor especially when management cost was considered. The comparison of the two cases in China and the UK, shows that design factors should be treated in a more stringent way instead of referring values from local standard authorities only which could induce overdesign of the buildings. Highlights: This article integrates system dynamics with energy performance simulation. This article tempts to quantify the effect of social factors on building performance gap. This article documents well the developed framework and detailed application process to a case study in China. This article provides a possible solution to help developers to improve actual building performance.